Ecoanxiety and mental health unveiled: a bibliometric analysis - Abdullah, Khairul Hafezad; Azizan, Azliyana (International Journal of Public Health Science (IJPHS), 2024)
Ecoanxiety, which encompasses the psychological impacts of environmental change, has emerged as a pressing global concern. However, the complex interrelationship between environmental factors and mental health in the context of ecoanxiety remains underexplored. This bibliometric analysis examines the evolution of international research on ecoanxiety and mental health using the Scopus and Web of Science databases. Parameters analyzed include publication trends over time, contributing countries, research foci, and keyword frequencies related to climate change, ecoanxiety, mental health, and solastalgia. The findings reveal surging scholarship in recent years, exponential publication growth, and increasing international collaborations. The total of 214 documents initially retrieved, 122 peer-reviewed publications met the inclusion criteria after pre-processing. The analysis provides a comprehensive overview of the current state of ecoanxiety and mental health research. It elucidates patterns in the emergence and progression of this burgeoning field to inform future research directions. Specifically, the elucidated features regarding keyword usage and research trends establish a foundation to advance investigations on the nexus between environmental issues and psychological well-being. This bibliometric study synthesizes existing knowledge and unveils fruitful avenues to progress understanding of the psychological ramifications of ecological crises.